HAPPINESS AS A LEARNING PROCESS - Wahyu Rahardjo (Universitas Gunadarma, 2007)
Happiness is one of the most meaningful positive emotion dan related to motivation to do many things. In order to gain happiness, a lot of people become passive and not going to do anything. In fact, there are many simple things to do to feel the flow experiences and get happiness. This might be happened because happiness is an adaptive behavior that can be learned by anybody. When someone recognize that happiness is something to be realized he/she should fight for his/her happiness by starting little fun things.Key words: happiness, adaptive behavior, learned behavior, flow experiences